Inclusion of Probiotic on Chicken Performance and Immunity: A Review - Mahfuz, S.U.; Nahar, M.J.; Mo, Chen; Ganfu, Zhang; Zhongjun, Liu; Hui , Song (International Journal of Poultry Science, 2017)
Supplementation of probiotic as a mean to improve the health and performance of poultry has generated significant interest over the last few years. A driving force for the interest of probiotic is to eliminate the use of low-dose antibiotics in poultry production. The extensive use of antibiotics in poultry with the purpose of promoting growth rate, increasing feed conversion efficiency and for the prevention of intestinal infections have led to an imbalance of the beneficial intestinal flora and the appearance of resistant bacteria. With increasing concerns about antibiotic resistance, there is increasing interest in finding alternatives to antibiotics for poultry production. To avoid the health hazards of antimicrobials drugs like antibiotics to human as well as poultry, probiotic has been used for as an potential substitute for antibiotics and been proved to be saved in poultry production system. This increased attention toward probiotic supplementation has generated an extensive body of research in the present day. However, there is still a lot of debate in scientific literature regarding the significant effect of probiotic on immune response against specific pathogens and growth performance in poultry. Taking into account the experimental immune responses and performance, this review provides a summary of the use of probiotic for prevention of infectious diseases in poultry, as well as demonstrating the potential role of probiotic in the growth performance and immune response of poultry, with a critical evaluation of results obtained to date. Collectively this study found a strong evidence to suggest that probiotic supplementation may have an impact on the immune response, overall health and performance of poultry.